The Effectiveness of Supervision on Management of Hazardous and Toxic Waste at RSUD Labuang Baji in Makassar City - Herlina Sakawati; Amihara Amihara; sulmiah Sulmiah (Universitas Negeri Makassar, 2021)
This study aims to determine the effectiveness of Supervision the management of hazardous and toxic waste / bahan berbahaya dan beracun (B3) at the RSUD (Rumah Sakit Umum Daerah) Labuang baji in Makassar City, which can be identified through indicators of measuring tools (standards), assessment and repair. This type of research is qualitative research with data collection techniques, namely interviews, observations and documentation. The data validity was checked by triangulation and member check. Data analysis techniques use data condensation, data presentation and conclusion drawing. The results of this study indicate that the supervision carried out by the Makassar City Environmental Agency on B3 waste management at Labuang Baji Hospital is running effectively. This can be seen from the determination of B3 waste management standards that do not cross the limit of B3 waste produced by Labuang Baji Hospital. In addition, the implementation of assessments in the form of direct visits conducted by the Makassar City Environment Office to Labuang Baji Hospital every year and the improvement actions carried out by the Makassar City Environment Office in the form of a direct reprimand to labuang baji hospital.